2011
DOI: 10.2478/s11535-011-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic potency of stem cell-based genetic engineering targeting Wnt3a and Wnt9a

Abstract: Bone engineering is a promising therapeutic approach to correct skeletal defects, and genetically-modified stem cells have been implicated in engineering new bone. However, the use of genetically-modified human mesenchymal stem cells targeting an osteogenic growth factor Wnt is not yet investigated. In the present study, a proliferation assay and the alkaline phosphatase (ALP) activity and expression of runt-related transcription factor 2 (Runx2) and osteocalcin (OC) transcripts were investigated to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Interestingly, Wnt9a expression was shown to be downregulated during the differentiation of precursor cells into mature osteoblasts, and knockdown of Wnt9a in osteoblasts increased expression of ALP, runx2, a key transcription factor for osteoblast differentiation, and osteocalcin, a late marker of osteoblast differentiation [32, 33]. In addition, knockdown of Wnt9a in osteoblasts increased their degree of mineralization [33], indicating that Wnt9a is an inhibitor of osteoblast differentiation. PCR array analysis revealed that the Wnt receptors Fzd1, 2, 3, 4, 5, 6, 7, and Lrp5 and Lrp6 were expressed in WT BMSCs cultured for 2 days in osteogenic differentiation medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wnt9a expression was shown to be downregulated during the differentiation of precursor cells into mature osteoblasts, and knockdown of Wnt9a in osteoblasts increased expression of ALP, runx2, a key transcription factor for osteoblast differentiation, and osteocalcin, a late marker of osteoblast differentiation [32, 33]. In addition, knockdown of Wnt9a in osteoblasts increased their degree of mineralization [33], indicating that Wnt9a is an inhibitor of osteoblast differentiation. PCR array analysis revealed that the Wnt receptors Fzd1, 2, 3, 4, 5, 6, 7, and Lrp5 and Lrp6 were expressed in WT BMSCs cultured for 2 days in osteogenic differentiation medium.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings show that lack of ANK function results in decreased expression of several Wnt ligands, Wnt receptors and Wnt signaling proteins in BMSCs when cultured in osteogenic differentiation medium that have been shown to stimulate Wnt/β-catenin signaling in these cells and ultimately osteogenesis [14]. In contrast, Wnt9a, a Wnt ligand that has been shown to inhibit osteogenesis was increased in ank/ank BMSCs [33]. These findings suggest that the increased expression of ANK during early osteogenesis is a key mediator of stimulating the expression of Wnt ligands and receptors, including Lrp5 and Lrp6, key co-receptors for the activation of Wnt/β-catenin signaling, and Wnt signaling proteins that are required for osteogenic fate decision of adult mesenchymal stem cells [15].…”
Section: Discussionmentioning
confidence: 99%